Painful Poison - Arnold, Nick (Horrible Science, 2008)
Discover how can you turn your brother into a zombie slave and why you are breathing poison right now! With a fantastic new cover look and extra horrible bits at the back of the book, this best-selling title is sure to be a huge hit with a new generation of Horrible Science readers.